DAMPAK PEMBANGUNAN APARTEMEN X TERHADAP LINGKUNGAN HIDUP DI RAWA BUNTU - Resta Apriatami (FT-USNI, 2021)
development will definitely produce positive and negative impacts. In the Technical Material for the RTRW (Regional Spatial Plan) of South Tangerang City, Rawa Buntu Village which is included in Serpong District; is an area that is included in the cultivation area which is intended for medium density housing. The research was conducted on the X Apartment construction project which is located in the Rawa Buntu Station area. The impact of the construction of the apartment is in the form of physical impacts and socio-economic impacts. The physical impacts are in the form of vibration, noise, and dust. Meanwhile, the socio-economic impacts that occur are travel barriers or traffic jams, potholes and slippery roads, as well as impacts on the economy of the community around the project. The social impacts that occur are the absorption of labor from the environment around the project, as well as easy access to transportation for the people who will live in the apartment; which includes a positive impact. The initiator undertakes efforts to overcome negative physical impacts by regulating working hours; and countermeasures for dust is to use a bulkhead or project barrier. As for the negative social impacts that the project proponent has overcome, namely the construction of roads that are The community has a role and involvement that is recognized by the proponent. It can be seen from the beginning of the development project that the initiator socializes the project to the community. The proponent is also responsive in overcoming negative impacts by responding to complaints from the surrounding community by immediately improving the environment affected by the development project.